2013
DOI: 10.1021/jo400389h
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Photophysical Properties of Difluoroboron Complexes of Curcuminoid Derivatives Bearing Different Terminal Aromatic Units and a meso-Aryl Ring

Abstract: The synthesis of nine curcuminoids and their difluoroboron complexes is described, with seven of them containing a meso-phenyl ring. Dynamic (19)F NMR confirmed the fact that rotation of that meso-aryl fragment is restricted in the latter systems at room temperature and become allowed at higher temperature (>45 °C). The molecular structure of a meso-substituted derivative in the solid state showed that the phenyl ring lies in a highly twisted plane with respect to the mean curcuminoid plane. The photophysical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
88
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(95 citation statements)
references
References 65 publications
7
88
0
Order By: Relevance
“…The data for 4, 9, 12, 13, 14, 17, 24, 25, 26, 27, 29 were reported previously by some of us. [32][33][34][35][36] Those for 6, 7, 8 were published by other groups. 27,28 For the sake of comparison, we recorded the spectra of the last three compounds under the same experimental conditions using DCM as solvent and the data we obtained are fully consistent with the published ones.…”
Section: Fluorescence Emission Propertiesmentioning
confidence: 99%
See 3 more Smart Citations
“…The data for 4, 9, 12, 13, 14, 17, 24, 25, 26, 27, 29 were reported previously by some of us. [32][33][34][35][36] Those for 6, 7, 8 were published by other groups. 27,28 For the sake of comparison, we recorded the spectra of the last three compounds under the same experimental conditions using DCM as solvent and the data we obtained are fully consistent with the published ones.…”
Section: Fluorescence Emission Propertiesmentioning
confidence: 99%
“…In our recent studies, [32][33][34][35] we showed that the unique linear and nonlinear optical properties of borondiuoride complexes of curcuminoids also stem from the combination of electron donor (D) and acceptor (A) units in a D-A-D quadrupolar-like architecture in which A is the central dioxaborine ring and D is a terminal aromatic moiety acting as an electron donor substituent. As such, these compounds are highly solvatochromic dyes and their emission wavelengths can be tuned over the entire visible spectrum up to NIR region by controlling the strength of the terminal donor group.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…This sequence is found consistent with that noticed for BF2 complexes of curcuminoids bearing the same series of terminal aryl groups. [16] However, steady-state fluorescence spectroscopy shows a peculiar behavior for 2 and even more for 3. Compound 2 emits at the longest wavelength (576 nm) while the spectrum of 3 is considerably blue-shifted relative to that of 1.…”
Section: Uv-vis and Fluorescence Emission Properties In Solutionmentioning
confidence: 99%